Buckypapers in Polymer-Based Nanocomposites: A Pathway to Superior Thermal Stability - Johannes Bibinger; Sebastian Eibl; Hans-Joachim Gudladt; Philipp Höfer (Nanomaterials)
The thermal stability of carbon fiber-reinforced plastic (CFRP) materials is constrained by the low thermal conductivity of its polymer matrix, resulting in inefficient heat dissipation, local overheating, and accelerated degradation during thermal loads. To overcome these limitations, composite materials can be modified with buckypapers—thin, densely interconnected layers of carbon nanotubes (CNTs). In this study, sixteen 8552/IM7 prepreg plies were processed with up to nine buckypapers and strategically placed at various positions. The resulting nanocomposites were evaluated for manufacturability, material properties, and thermal resistance. The findings reveal that prepreg plies provide only limited matrix material for buckypaper infiltration. Nonetheless, up to five buckypapers, corresponding to 8 wt.% CNTs, can be incorporated into the material without inducing matrix depletion defects. This integration significantly enhances the material’s thermal properties while maintaining its mechanical integrity. The nanotubes embedded in the matrix achieve an effective thermal conductivity of up to 7 W/(m·K) based on theoretical modeling. As a result, under one-sided thermal irradiation at 50 kW/m2, thermo-induced damage and strength loss can be delayed by up to 20%. Therefore, thermal resistance is primarily determined by the nanotube concentration, whereas the arrangement of the buckypapers affects the material quality. Since this innovative approach enables the targeted integration of high particle fractions, it offers substantial potential for improving the safety and reliability of CFRP under thermal stress.